Curcumin Stereoisomer, Cis-Trans Curcumin, as a Novel Ligand to A1 and A3 Adenosine Receptors - Luke J. Hamilton; Mahesh Pattabiraman; Haizhen A. Zhong; Michaela Walker; Hilary Vaughn; Surabhi Chandra (MDPI AG, 2023)
Adenosine receptors (ARs) are being explored to generate non-opioid pain therapeutics. Vanilloid compounds, curcumin, capsaicin, and vanillin possess antinociceptive properties through their interactions with the transient receptor potential channel family. However, their binding with adenosine receptors has not been well studied. The hypothesis in this study was that a vanilloid compound, cis-trans curcumin (CTCUR), binds to each of the two Gi-linked AR subtypes (A1AR and A3AR). CTCUR was synthesized from curcumin (CUR) using the cavitand-mediated photoisomerization technique. The cell lines transfected with the specific receptor (A1AR or A3AR) were treated with CTCUR or CUR and the binding was analyzed using competitive assays, confocal microscopy, and docking. The binding assays and molecular docking indicated that CTCUR had Ki values of 306 nM (A1AR) and 400 nM (A3AR). These values suggest that CTCUR is selective for Gi-linked ARs (A1AR or A3AR) over Gs-linked ARs (A2AAR or A2BAR), based on our previous published research. In addition, the docking showed that CTCUR binds to the toggle switch domain of ARs. Curcumin (CUR) did not exhibit binding at any of these receptors. In summary, CTCUR and other modifications of CUR can be developed as novel therapeutic ligands for the Gi-linked ARs (A1AR and A3AR) involved with pain and cancer.